2022
DOI: 10.1007/s10904-022-02417-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glycerin on Electrical and Thermal Properties of PVA/Copper Sulphate Gel Polymer Electrolytes

Abstract: Copper-ion conducting gel polymer electrolyte (GPE) systems based on polymer poly(vinyl alcohol) (PVA) and copper sulphate salt doped with glycerin as plasticizer have been synthesized by using solution casting method. Differential scanning calorimetry is used to examine the thermal effect of glycerin on a plasticized polymer electrolyte (DSC). With the addition of various quantities of glycerin, as a plasticizer in pure PVA and PVA+20wt.%CuSO 4 gel polymer electrolyte shows a decrease in the values of melting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The enhanced low‐frequency permittivity is attributed to the excessive charge carriers' inhibiting effect at the interfaces facilitating the IP, and the high‐frequency one is also enhanced owing to the construction of insulating PS shell promoting the intraparticle quick polarization of Zn@ZnO@PS. Thus, the use of the second PS interlayer synchronously promotes the slow IP at lower frequencies and the fast intraparticle polarization at higher frequencies thereby showing much high permittivity than other cases 41,43 . Furthermore, it is revealed that the PS thickness possesses an evident impact on the permittivity of composites, and at an optimal PS thickness like Zn‐3 the highest permittivity can be reached due to maximally induced IP effect in the composites.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The enhanced low‐frequency permittivity is attributed to the excessive charge carriers' inhibiting effect at the interfaces facilitating the IP, and the high‐frequency one is also enhanced owing to the construction of insulating PS shell promoting the intraparticle quick polarization of Zn@ZnO@PS. Thus, the use of the second PS interlayer synchronously promotes the slow IP at lower frequencies and the fast intraparticle polarization at higher frequencies thereby showing much high permittivity than other cases 41,43 . Furthermore, it is revealed that the PS thickness possesses an evident impact on the permittivity of composites, and at an optimal PS thickness like Zn‐3 the highest permittivity can be reached due to maximally induced IP effect in the composites.…”
Section: Resultsmentioning
confidence: 89%
“…Thus, the use of the second PS interlayer synchronously promotes the slow IP at lower frequencies and the fast intraparticle polarization at higher frequencies thereby showing much high permittivity than other cases. 41,43 Furthermore, it is revealed that the PS thickness possesses an evident impact on the permittivity of composites, and at an optimal PS thickness like Zn-3 the highest permittivity can be reached due to maximally induced IP effect in the composites.…”
Section: Dielectric Propertiesmentioning
confidence: 98%
“…Charge carrier mobility, charge carrier concentration, the impact of space charge, carrier hopping in the localized state, and charge carrier stimulation to higher states in the conduction band may all be responsible for the increase in conductivity that occurs with an increase in AgNPs volume percent. [ 34,41 ]…”
Section: Resultsmentioning
confidence: 99%
“…24 It should be noted that the crystallinity of a polymeric material can be altered by heat treatment. [25][26][27] When the temperature rises above the polymer glass transition temperature, the polymer crystallinity is reduced. 28,29 The heat treatment of the produced electrospun nanofibers is proven feasible to increase its transparency.…”
Section: Introductionmentioning
confidence: 99%